Coronary Artery Bypass Grafting Using Total Arterial Conduit (Lima-Rima) on a Young Female: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2026)
Background : Coronary Artery Bypass Grafting (CABG) although commonly done in our population, there is an alarming increase of young candidates for CABG now-adays.  Evidence suggests, young patients are more benefitted with total arterial grafts. But, total arterial grafts in the form of bilateral mammary artery harvesting may provoke sternal complications especially in the women.Case Presentation: We have successfully treated a young diabetic, female patient in our center with bilateral mammary grafting without any complications and after months of follow-up patient is leading a symptom free  life. As per our knowledge this is the first reported case of  Bilateral Internal mammary Artery (BIMA) grafting in a female patient in our institute.Conclusion: Through augmented preparation Bima grafting can be safely done in females in indicated cases keeping careful consideration of potential sternal healing issues.JCMCTA 2025 ; 36 (2) : 165-167